PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN SOLVABILITAS TERHADAP AUDIT DELAY (Studi Pada Perusahaan-Perusahaan LQ 45 Sektor Pertambangan Yang Terdaftar di Bursa Efek Indonesia Periode 2012-2018) - Ghonimah Zumroatun Ainiyah; Yogka Arief Pratama; Ellan Budiarti (Program Studi Akuntansi, Universitas Kuningan, 2021)
The LQ 45 companies in the mining sector is one of the pillars of economic activity in Indonesia and is used as an investment, so the company's audit report must be completed on time because these financial statements are needed when making decisions by investors regarding their investment activities. However, there are still some companies that are late in reporting their audit reports. The aim is to examine the effect of firm size, profitability, and solvency on audit delay. Use total asset indicators for firm size, ROA for profitability, and DAR for solvability.Mining sector is one of the pillars of Indonesian economic activity and become a strategic option for investors. As a result the company's audit report must be announced on schedule. LQ 45 as part of mining sector that has an important role for investing. This study aims to know whether firm size, profitability, and solvability affect audit delays. It used total asset indicators for firm size, ROA for pIn this study were secondary data which was obtained from the financial statements of LQ 45 listed on BEI during 2012-2018 period. The sampling technique used purposive sampling. Data analysis in this research used is multiple regression analysis with SPSS 24.The results showed firm size and profitability did not affect in audit delay, solvability affected in audit delay. Firm size, profitability and solvability simultaneosuly affected audit delay as much as 48.9% and the remaining 51.1% was affected by other variables excluded in this study.Keywords: audit delay, firm size, profitability, solvability